Seats used by King George V and Queen Mary - Ghosh, Ayan (2023)
The two chairs used to sit during prayer services by King George and Queen Mary are marked with commemorative brass plaques with the date of their visit to St. Thomas Church. The royal couple had arrived in Mumbai onboard the steamship RMS Medina, and after spending a few days in Mumbai, they left by train to attend the Delhi Durbar.